Global stakeholder vision for ecosystem‐based marine aquaculture expansion from coastal to offshore areas. (14th March 2020) - Galparsoro, Ibon; Murillas, Arantza; Pinarbasi, Kemal; Sequeira, Ana M.M.; Stelzenmüller, Vanessa; Borja, Ángel; O´Hagan, Anne Marie; Boyd, Adele; Bricker, Suzanne; Garmendia, Joxe Mikel; Gimpel, Antje; Gangnery, Aline; et al.
Abstract: Marine aquaculture is the most promising industry for ensuring future provision of seafood. Yet, the worldwide growth and expansion of this industry have been slower than expected, calling for the identification of environmentally suitable sites while accounting for all factors that could constrain or benefit its establishment. Here, we determine the main obstacles and risks hindering the growth and expansion of marine aquaculture, as well as the needs and recommendations to overcome such constraints. Our analysis is based on results obtained from a consultation process held in 16 study sites located around the world with the participation of 614 stakeholders representing the research community, aquaculture industry, government, conservation groups, and education and fishermen associations. A high level of commonality exists in the main issues hindering aquaculture growth and expansion in coastal, off‐the‐coast and offshore aquaculture with most being attributed to interactions with other maritime activities, including conflicts with other users and administrative procedures, including licensing. Critical needs for improved management and expansion of the aquaculture industry are related to planning and management of developments and technological advances, with economic and market needs featuring to a lesser extent. Key procedures recommended to assist further aquaculture growth are the standardisation and simplification of regulatory frameworks, improvement of governance, and the adoption of participatory processes to facilitate meaningful and productive stakeholder engagement. We strongly recommend stakeholder participation to enhance insights on the full environmental and human dimensions of marine management and for implementation of ecosystem‐based marine spatial planning.